Oral Versus Intragastric Inoculation: Similar Pathways of Trypanosoma cruzi Experimental Infection? From Target Tissues, Parasite Evasion, and Immune Response - Barreto de Albuquerque, Juliana; Silva dos Santos, Danielle; Stein, Jens V.; de Meis, Juliana (Frontiers in Immunology, 2018)
Oral infection has become the most important transmission mechanism of Chagas disease in Brazil and others Latin American countries. Increased mortality rate is marked in the first 2 weeks, surpassing the calculated mortality produced by the disease resulting from the biting of infected insect vectors. Thus, the oral route of T. cruzi infection, and the consequences in the host must be taken into account when thinking on the mechanisms underlying the natural history of the disease. Distinct routes of parasite entry may affect differentially on immune circuits, stimulating regional immune responses that impact on the overall profile of the host protective immune response. Experimental studies related to oral infection usually comprise inoculation in the mouth (oral infection, OI) or gavage (gastrointestinal infection, GI), being often considered as similar routes of infection. Hence, establishing a relationship between the inoculation site (OI or GI) with disease progression and the mounting of T. cruzi-specific regional immune responses is an important issue to be considered. Here, we provide a discussion on studies performed in OI and GI in experimental models of acute infections, including T. cruzi infection.